Flavonoid Naringenin Alleviates Short-Term Osmotic and Salinity Stresses Through Regulating Photosynthetic Machinery and Chloroplastic Antioxidant Metabolism in Phaseolus vulgaris - Yildiztugay, Evren; Ozfidan-Konakci, Ceyda; Kucukoduk, Mustafa; Turkan, Ismail (Frontiers in Plant Science, 2020)
The current study was conducted to demonstrate the possible roles of exogenously applied flavonoid naringenin (Nar) on the efficiency of PSII photochemistry and the responses of chloroplastic antioxidant of salt and osmotic stressed-Phaseolus vulgaris (cv. Yunus90). For this aim, plants were grown in hydroponic culture and were treated with Nar (0.1 and 0.4 mM) alone or in combination with salt (100 mM NaCl) and/or osmotic (10% Polyethylene glycol, -0.54 MPa). Both of stress caused a reduction in water content (RWC), osmotic potential (), chlorophyll fluorescence (Fv/Fm) and potential photochemical efficiency (Fv/Fo). Nar reversed the changes on these parameters. The phenomenological fluxes (TRo/CS and ETo/CS) altered by stress were induced by Nar and led to a notable increase in the performance index [PIABS] and the capacity of light reaction [Po/(1-Po)]. Besides, Nar-applied plants exhibited higher specific fluxes values (ABS/RC, ETo/RC and Eo/(1-Eo)) and decreasing controlled dissipation of energy (DIo/CSo and DIo/RC). The transcripts levels of psbA and psbD were lowered in stress-treated bean, but upregulated in Nar-treated plants after stress exposure. Nar also alleviated the changes on gas exchange parameters [carbon assimilation rate (A), stomatal conductance (gs), intercellular CO2 concentrations (Ci), transpiration rate (E) and stomatal limitation (Ls)]. By regulating the antioxidant metabolism of isolated chloroplasts, Nar was able to control the toxic levels of hydrogen peroxide (H2O2) and TBARS (lipid peroxidation) produced by stresses. Chloroplastic superoxide dismutase (SOD) activity reduced by stresses was increased by Nar. In response to NaCl, Nar increased the activities of ascorbate peroxidase (APX), glutathione reductase (GR), monodehydroascorbate reductase (MDHAR) and dehydroascorbate reductase (DHAR) as well as peroxidase (POX). Nar protected the bean chloroplasts by minimizing disturbances caused by NaCl exposure via the ascorbate (AsA) and glutathione (GSH) redox-based systems. Under Nar plus PEG, Nar maintained the AsA regeneration by the induction of MDHAR and DHAR, but not GSH re-cycling by virtue of no induction in GR activity and the reduction in GSH/GSSG and GSH redox state. Based on these advances, Nar protected in bean chloroplasts by minimizing disturbances caused by NaCl or PEG exposure via the AsA or GSH redox-based systems and POX activity.